The Zeitroman of the late Weimar Republic - Matijevich, Elke (Lang, 1995)
During the turbulent Weimar era, the Zeitroman emerged as a literary genre with sharp social and political criticism as its focus. Morally or ideologically engaged writers across the political spectrum - Willi Bredel, Hans Fallada, Irmgard Keun, Erich Kastner, and Ernst von Salomon among others - used current events to craft novels that sought to persuade a wide readership of the need to reform German society How did these novels present the lives of blue-collar workers, the petty bourgeoisie, women, intellectuals, and right-wing activists? How were they received by the press and the public? And why are many locked in the literary history of their period, while others find resonance beyond their own time and culture
Keywords: Fallada; Hans; Kästner; Erich; Keun; Irmgard; Salomon; Ernst von; Bredel; Willi; Duits; Histoire - Dans la littérature; Problèmes sociaux - Dans la littérature; Roman allemand - 20e siècle - Histoire et critique; Tijdromans; Écrivains allemands - 20e siècle - Pensée politique et sociale; Deutsch; Geschichte; Authors; German; German fiction; History in literature; Social problems in literature; Weimarer Republik; Zeitroman